Effects of changes in alpine grassland vegetation cover on hillslope hydrological processes in a permafrost watershed - Wang Genxu; Liu Guangsheng; Li Chunjie (Journal of Hydrology, 2012)
Two main types of grasslands on the Qinghai-Tibet Plateau, alpine swamp and alpine meadow, were selected for this study. Monitoring plots were constructed on each type of grassland with varying degrees of vegetation degradation. The impacts of alpine grassland cover changes on the hillslope water cycle were analyzed in terms of runoff generation, precipitation interception, dew water formation, and soil water dynamics of the active layer, etc. The results showed that different types of grasslands led to different runoff generation regimes; namely, runoff varied linearly with precipitation in alpine swamp, whereas in alpine meadow, runoff exhibited an exponential precipitation-dependence. The decrease in vegetation cover in alpine swamp leads to a decrease in soil moisture content in the top 20 cm of the soil, a delay in the thawing start time in the spring, and a decrease in both surface runoff and subsurface interflow. In alpine meadow, however, the decrease in vegetation cover led to a significant increase in the depth of topsoil moisture content during the thawing period, earlier occurrence of thawing, and an increase in the runoff generation ratio. The alpine meadow vegetation canopy had a higher maximum interception ratio and saturation precipitation than alpine swamp vegetation. With the decrease in vegetation cover, the rainfall interception ratios decreased by almost an identical range in both the alpine meadow and alpine swamp grasslands. Dew water commonly occurs on alpine grassland, accounting for about 12.5-16.5% of precipitation in the same period, and thus, is an important component of the water cycle. With the degradation of vegetation, surface dew water decreased; however, the ratio of dew water formed in the air to the total amount of dew water rose significantly. At the hillslope scale, the changes of alpine vegetation cover had a great influence on the water cycle, which were partly attributed to that the changes of alpine vegetation cover directly altered the surface energy balance, surface ...